Using a non-recursive model with feedback loops to identify barriers to learning as a dynamic construct in workplace learning - Anselmann, Sebastian [Verfasser]; Anselmann, Veronika [Verfasser] (My University, 2026)
"Barriers to learning in the workplace form a holistic set of missing individual, team, and organizational aspects that hinder the initiation of successful learning, interrupt learning possibilities, delay proceedings, or end learning activities much earlier than intended. These barriers ultimately determine the way individuals seek learning opportunities in the workplace. Based on an explorative interview study and the development and validation of a measurement instrument for barriers to learning at the workplace, this cross-sectional questionnaire study (N = 230) was conducted to investigate barriers to learning as a dynamic construct in workplace learning. Factor analysis, analysis of Cronbach’s alpha, descriptive analyses, and structural equation modeling (SEM) of a non-recursive model with feedback loops were conducted to identify the dynamic aspects and interplay of barriers to learning with the factors job satisfaction and turnover intention. The non-recursive model with feedback loops (CFI = .98 and RMSR = .073) indicated that the relationship between barriers to learning with sub-categories such as individual components and organizational limitations are negatively related to job satisfaction and have an indirect effect on turnover intention. With this interdisciplinary contribution, trainings and work-based learning scenarios can be initiated to unlock the potential of learners that has been blocked due to previously under-researched barriers to learning." (Author's abstract ; BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; G 2.3.1 Arbeitsteilung & -organisation; 370; Lernen am Arbeitsplatz; Lernumgebung; Arbeitszufriedenheit; Arbeitsplatzwechsel; Interview